Minimal/Measurable Disease Analysis in Chronic Lymphocytic Leukemia/Small Lymphocytic Lymphoma by Flow Cytometry. Issue 8 (18th August 2022) - Gao, Qi; Roshal, Mikhail
Abstract: CLL/SLL is the most common leukemia in the western world. The disease is indolent; however, most patients require treatment at some point of the disease course. Outside of allogeneic transplants, the treatment is rarely curative but often controls CLL/SLL manifestations for many years. Several lines of therapy may be used sequentially to prolong clinical remission. Because of the prolonged disease course, CLL/SLL monitoring represents a sizable portion of the workload in a typical flow cytometry laboratory involved in the diagnosis and monitoring of hematopoietic neoplasms. Minimal/measurable disease monitoring of CLL/SLL has emerged as a key component in treatment monitoring and sequencing. In the face of effective therapies, clinical laboratories are tasked with monitoring ever smaller proportions of MRD with high precision and accuracy. With the recent addition of surface antigen–targeting biologics such as antibodies and CAR‐T cells, the task has become more complex due to the unavailability of commonly analyzed antigens for flow cytometric analysis. This article details a flow cytometric test developed at Memorial Sloan Kettering Cancer Center that has proven to consistently achieve high sensitivity (<0.01% of nucleated cells) in the bone marrow and peripheral blood, even when CD19 is lost or unavailable for analysis. Moreover, the test helps distinguish between CLL and other CD5‐positive B cell neoplasms. The Basic Protocol provides a detailed operational procedure for processing, staining, and cytometric acquisition of samples. The Support Protocol provides typical steps and caveats for MRD data analysis in CLL/SLL and in distinguishing CLL/SLL from other B cell neoplasms and normal CD5‐positive B cells. © 2022 Wiley Periodicals LLC. Basic Protocol : Processing, staining, and cytometric analysis of bone marrow or peripheral blood cells for MRD analysis of CLL/SLL Support Protocol : Analysis and interpretation of CLL MRD assay